Managing COVID-19 in a Large Urban Research-Intensive University. Issue 6 (2nd October 2020) - Regehr, Cheryl; Goel, Vivek
Abstract: While universities regularly face emergency situations that affect their operations, the global disruption caused by COVID-19 is unprecedented, presenting unique challenges to universities. This article describes the initial stages of crisis response at a large research-intensive university in the center of a diverse international city. Structural, operational, social/psychological, and communication challenges have shifted during five phases we experienced in COVID-19: preplanning, approaching crisis, immediate crisis, prolonged uncertainty, and planning for restart and recovery. Key to managing challenges is clear but flexible incident management structures, and constant interaction and collaboration among groups addressing varying aspects of the operation.